Socialisation Problems of Orphanage Children in the Republic of Kazakhstan - Ainur Sadyrova; Zhomart Simtikov; Nurlan Apakhayev (Space and Culture, India)
The study aims to address the socialisation process of children from orphanages in Kazakhstan to identify effective approaches to their adaptation and integration into society. The study examined various theoretical concepts of socialisation, including aspects of children’s adaptation to a new environment, personality development through social interaction, and the institutional environment's impact on social skills development. The dynamics of children's movement in Kazakhstan's social protection system in 2013-2022 were also addressed. The study's results included identifying key aspects of the socialisation of children from orphanages, namely adaptation to new social conditions, establishing trusting relationships, overcoming stigma and quality education. The study determined that to ensure the effective and equitable development of all the identified aspects, it is necessary to apply several approaches that, in interaction, can ensure the harmonious development of the child’s personality in all spheres of life. For this purpose, psychological, pedagogical and sociological approaches were chosen; their essence and desired effects on the orphans' socialisation process were revealed. The statistical information presented in the study on the movement of children from organisations for orphans and children without parental care in 2013-2022 showed a significant decrease in the number of children entering the protection system but also revealed a disproportionate decrease in the number of children leaving the system due to enrolment in higher education or other educational institutions. To address the problems of socialisation of children in orphanages, recommendations that include modern methods of working with orphans were developed. The results indicate the importance of using innovative programmes for the socialisation of children in orphanages and the need to consider the psychological consequences of depriving children of parental care.